Efektivitas Etelcalcitide terhadap Hiperparatiroidisme Sekunder Pada Pasien Gagal Ginjal Kronik - Muhammad Tola, Sakura (Lembaga Penelitian Universitas YARSI, 2018)
Secondary hyperparathyroidism (sHPT) is a frequently occurring severe complication ofadvanced kidney disease. Its clinical consequences include extraskeletal vascular and valvular calcifications, changes in bone metabolism resulting in renal osteodystrophy, and an increased risk of cardiovascular morbidity and mortality. Calcimimetics are a cornerstone of parathyroid hormone (PTH)-lowering therapy, as confirmed by the recently updated 2017 Kidney Disease: Improving Global Outcomes chronic kidney disease – mineral and bone disorder clinical practice guidelines. Contrary to calcitriol or other vitamin D-receptor activators, calcimimetics reduce PTH without increasing serumcalcium, phosphorus,or FGF23 levels. Etelcalcetide is a new second-generation calcimimetic that has been approved for the treatment of sHPT in adult hemodialysis patients. Where as the first-generation calcimimetic cinacalcet is taken orally once daily, etelcalcetide is given intravenously thrice weekly at the end of the hemodialysis session. Apart from improving drug adherence, etelcalcetide has proven to be more effective in lowering PTH when compared to cinacalcet, with an acceptable and comparable safety profile. The hope for better gastrointestinal tolerance with intravenous administration is no true, as etelcalcetide isn’t significantly mitigate the adverse gastrointestinal effects associated with cinacalcet. Enhanced adherence and strong reductions in PTH, phosphorus, and FGF23 can set the stage for a future large randomized controlled trial to demonstrate that improve biochemical control of mineral metabolism with etelcalcetide in hemodialysis patients translates into cardiovascular and survival benefits and better health-related quality of life.